Modal Analysis of the Turbine Blade at Complex Thermomechanical Loads - Witek, L.; Stachowicz, F. (Проблемы прочности, 2016)
The results of modal analysis of the turbine blade were presented. The turbine blade during the operation of the engine is subjected to complex thermomechanical loads induced by centrifugal forces of the rotating blade and a nonuniform thermal field. These loads have a great influence on the natural frequencies of the blade. In the first section of the study, modal analysis of the blade was performed using the vibration system. As a result, the resonant frequencies of the real blade were obtained. In order to check the effect of the rotational engine speed and the thermal field on the natural frequencies of the blade, the finite element method was employed. At the first stage of computations static analysis was conducted for the blade subjected to mechanical and thermal loads. Then modal analysis was used to isolate the natural frequencies and vibration modes of the blade. In modal analysis the stress state from the first stage was considered as preliminary conditions. Several results of numerical calculations and experimental analysis were compared to detect the relative error of natural frequency estimates